Methanol Stem Bark Extract of Tamarindus indica Exhibited Antidepressant Activity in Mice (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Depression is one of the most common psychiatric disorders affecting nearly 17% of the world population and the existing antidepressant drugs used in clinical settings are largely associated with serious side effects.  Tamarindus indica (Fabaceae) is a plant that has been used ethno-medicinally as a remedy for depression.Objectives: The objective of this study was to determine the antidepressant activity of methanol stem bark extract of Tamarindus indica using mice, also to determine the LD50 and phytoconstituents of same extract.Methods: Fresh leaves of Tamarindus indica were collected, pulverised and extracted using 70% v/v methanol. Phyto-constituents of the extract were screened and Median lethal dose (LD50) was determined using standard protocols. Antidepressant effects of the extract were investigated using Tail suspension test (TST) and forced swimming test (FST) models.Results: The results of median lethal dose revealed the LD50 value of 470 mg/kg body weight and the phytochemical screening showed the presence of saponins, alkaloids and glycosides.  The extract at the doses of 75 and 150 mg/kg body weight significantly (p
Keywords: Depression; Antidepressants; LD50; Tail Suspension Test; Forced Swimming Test